2021
DOI: 10.3389/fonc.2021.687672
|View full text |Cite
|
Sign up to set email alerts
|

The Time for Chronotherapy in Radiation Oncology

Abstract: Five decades ago, Franz Halberg conceived the idea of ​​a circadian-based therapy for cancer, given the differential tolerance to treatment derived from the intrinsic host rhythms. Nowadays, different experimental models have demonstrated that both the toxicity and efficacy of several anticancer drugs vary by more than 50% as a function of dosing time. Accordingly, it has been shown that chemotherapeutic regimens optimally timed with the circadian cycle have jointly improved patient outcomes both at the precli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 101 publications
(116 reference statements)
0
13
0
Order By: Relevance
“…As TIMELESS is a circadian gene, immune checkpoint inhibitor regimens may need to be optimally timed with a patient's intrinsic rhythms to improve outcomes. Currently, only chronoradiotherapy and chronochemotherapy have been investigated across several cancers [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…As TIMELESS is a circadian gene, immune checkpoint inhibitor regimens may need to be optimally timed with a patient's intrinsic rhythms to improve outcomes. Currently, only chronoradiotherapy and chronochemotherapy have been investigated across several cancers [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in times of sensitivity/resistance to irradiation were also observed in many clinical studies reviewed in. 47,48 Thus, morning radiotherapy tended to be best tolerated by the oral mucosa patients. 49 Patients with breast cancer who received radiotherapy early morning showed less skin reaction as compared with the group who received the radiotherapy late afternoon (after 3 PM).…”
Section: Conclusion and Translational Aspectsmentioning
confidence: 99%
“…Although individual studies demonstrated statistical significance, study designs varied widely, and the differences in how patients were grouped presents a major obstacle to forming a consensus of strong conclusions [131]. It has been suggested that future time-of-day studies should compare groups of patients who received radiation within different narrow time windows that are separated by a few hours [149], rather than dividing groups by arbitrary cutoff times. This would ensure consistent differences in the timing of doses between patients of different groups.…”
Section: Limitations Of Past Researchmentioning
confidence: 99%